Academic systems, career models, and experienced performance pressure—a comparative study of Sweden and Finland - Kallio, Tomi J.; Lehtivuori, Aki; Kallio, Kirsi-Mari; Tienari, Janne; Funck, Elin (Springer Nature, 2026)
As universities compete for higher standings in global rankings and implement performance management measures, performance pressure is imposed on scholars. This paper explores the influence of academic systems and career models on scholars in Sweden and Finland, with a focus on experienced performance pressure. Comparable qualitative and quantitative data from these Nordic countries were collected. Despite their numerous similarities, the external contingency factors related to academic systems and career models differ between Sweden and Finland. We found that due to systemic differences the nature of experienced performance pressure differs between the two countries. While scholars in both countries experience high pressure related to performance management, the analysis indicates that the Swedish system primarily directs the pressure to the organizational level, whereas the Finnish system causes more explicit and intense individual level performance pressure. The analysis further indicates that the disparities are most pronounced in the experiences of scholars on fixed-term contracts. The paper suggests that the most decisive characteristic of performance pressure in scholarly work is not its overall magnitude but its nature and intensity from the perspective of individual scholars.